Subclinical hypothyroidism as a cause of leg swelling in patients attending tertiary level hospital in Kathmandu (Journal of Pathology of Nepal, 2018)
Background: Peripheral edema is one of the common causes of visit to medical outpatient department. After history taking and investigations few patients are left without diagnosis. This study was designed to find if there is any association between pedal edema and subclinical hypothyroidism when there is no other systemic disease is found.Materials and Methods: This is a cross-sectional observational hospital based study done in one of Medical colleges in Kathmandu for a period of 2 years .All patient coming to medical OPD for the first time with bilateral painless limb swelling were evaluated data were tabulated and analyzed using Ms Excel.Results: Out of 300 patients, 146 patients were exclude from history and clinical evaluation, 154 patients underwent laboratory evaluation. After investigations 46 patients were left without any other systemic disease. Out of them only 3 were male. About 40% of them are overweight or obese. 57% of them had high TSH level, which was significantly associated with limb swelling (t=0.012)Conclusion: Subclinical hypothyroidism is significantly associated with painless bilateral limb swelling when there is no other systemic cause. It is logical to investigate a limb swelling with thyroid function test however there needs to be a larger interventional study to exactly point out the cause in these patients.